2011
DOI: 10.1002/aoc.1772
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, microwave-promoted catalytic activity in Suzuki-Miyaura cross-coupling reactions and antimicrobial properties of novel benzimidazole salts bearing trimethylsilyl group

Abstract: A mixture of benzimidazole salts (2-7), Pd(OAc) 2 and K 2 CO 3 in DMF-H 2 O catalyzes the Suzuki-Miyaura cross-coupling reactions promoted by microwave irradiation resulting in high yield within a short time. In particular, the yield of the Suzuki-Miyaura reactions with aryl bromides was found to be nearly quantitative. The synthesized benzimidazole salts (2-7) were identified by 1 H-13 C, NMR, IR spectroscopic methods and microanalysis. The molecular structure of 1 was determined by X-ray crystallography. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 47 publications
2
31
1
4
Order By: Relevance
“…In recent years, considerable attention has been given to the synthesis of benzimidazole derivatives because of their various pharmacological activities such as antitumour, anti-ulcer, antibacterial, and antifungal properties [25][26][27][28][29][30][31][32]. Although there are different antibacterial and antifungal drugs used in the treatment of bacterial and fungal infections, some of them have undesirable side effects [33].…”
mentioning
confidence: 99%
“…In recent years, considerable attention has been given to the synthesis of benzimidazole derivatives because of their various pharmacological activities such as antitumour, anti-ulcer, antibacterial, and antifungal properties [25][26][27][28][29][30][31][32]. Although there are different antibacterial and antifungal drugs used in the treatment of bacterial and fungal infections, some of them have undesirable side effects [33].…”
mentioning
confidence: 99%
“…Furthermore, control experiments showed that the coupling reaction did not occur in 5 min in the absence of bis-benzimidazole salts. Another set of benzimidazole salts, containing a trimethylsilylmethyl substituent (BIm3), were then synthetized by the same authors (Scheme 37) [71]. The reported SMC reactions were performed using 300 W power MW irradiation at 120 °C in 10 min with a mixture of benzimidazole salts (2 mol promoted by various heating sources, such as MW and infrared.…”
Section: Ligands In Mw-assisted Smcmentioning
confidence: 99%
“…Another set of benzimidazole salts, containing a trimethylsilylmethyl substituent (BIm 3 ), were then synthetized by the same authors (Scheme 37) [71]. The reported SMC reactions were performed using 300 W power MW irradiation at 120 • C in 10 min with a mixture of benzimidazole salts (2 mol %), Pd(OAc) 2 (1 mol %) and K 2 CO 3 in DMF-H 2 O (1:1).…”
Section: Scheme 35 Novel Bis-benzimidazole Salts Bearing Furfuryl Anmentioning
confidence: 99%
“…Other examples can also be found, where MW irradiation proved to be beneficial in Suzuki-Miyaura cross-couplings by shortening the reaction times (usually to minutes), and increasing the yields, as compared to those obtained by traditional heating [8,[11][12][13].…”
Section: Suzuki-miyaura Reactionmentioning
confidence: 99%